2008
DOI: 10.1128/aac.00067-08
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Suppression of Hepatitis B Virus Replication by Short Hairpin RNA Expression Using the Scaffold/Matrix Attachment Region-Based Replicating Vector System pEPI-1

Abstract: Since the emergence of viral resistance of hepatitis B virus (HBV) during treatment is becoming an important issue even with newer drugs, there is a need for alternative treatment options such as, for example, RNA interference (RNAi) technology. While short-term suppression of HBV replication is easily achieved with small interfering RNA oligonucleotides, this is not the case for long-term suppression due to the lack of an optimal vector system. Based on the nonviral scaffold/matrix attachment region (S/MAR)-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…The expression level of a reporter gene when two β-globin MARs are flanked by a chloramphenicol acetyltransferase (CAT) expression cassette is significantly higher than that when one β-globin MAR is flanked by a CAT expression cassette in stably transfected Chinese hamster ovary (CHO) cells (Wang et al, 2010). Numerous MARs that improve foreign gene expression are currently used in gene therapy (Argyros et al, 2008;Jenke et al, 2008;Wong et al, 2010). One of the major problems associated with the majority of gene therapy protocols is the requirement of sustaining expression while a transgene is being integrated into a chromosome.…”
Section: Introductionmentioning
confidence: 99%
“…The expression level of a reporter gene when two β-globin MARs are flanked by a chloramphenicol acetyltransferase (CAT) expression cassette is significantly higher than that when one β-globin MAR is flanked by a CAT expression cassette in stably transfected Chinese hamster ovary (CHO) cells (Wang et al, 2010). Numerous MARs that improve foreign gene expression are currently used in gene therapy (Argyros et al, 2008;Jenke et al, 2008;Wong et al, 2010). One of the major problems associated with the majority of gene therapy protocols is the requirement of sustaining expression while a transgene is being integrated into a chromosome.…”
Section: Introductionmentioning
confidence: 99%
“…Jenke et al. 48 reported a novel non‐viral scaffold or matrix attachment region‐based vector system pEPI‐1. HBV RNA expression was reduced by 85 percent and 70 percent at 3 and 8 months after transfection with pEPI‐RNAi, respectively.…”
Section: Application Of Long‐term Rnai To Hbvmentioning
confidence: 99%
“…Secreted HBsAg was reduced by 94.2 percent in the cell culture and 84.5 percent in mouse serum, whereas the immunohistochemical detection of the HBV core antigen (HBcAg) revealed a more than 99 percent reduction in stained hepatocytes upon RNAi treatment. Jenke et al 48 reported a novel non-viral scaffold or matrix attachment region-based vector system pEPI-1. HBV RNA expression was reduced by 85 percent and 70 percent at 3 and 8 months after transfection with pEPI-RNAi, respectively.…”
Section: Application Of Long-term Rnai To Hbvmentioning
confidence: 99%
“…[1][2][3][4] Despite this, the use of involved field radiation is still often questioned with respect to out-of-field radiation dose, especially to the critical organs in close proximity, namely breasts in female patients. Although multiple publications addressed the out-of-field dose, [5][6][7][8][9] there is a paucity of data in the literature addressing specifically the dose to the breasts in young female patients with HL treated with modern field radiation therapy. We undertook this study to determine the dose of radiation to the breasts located in close proximity of a mediastinal radiation field, using an anthropomorphic phantom.…”
Section: Introductionmentioning
confidence: 97%